Unprovoked crying spells in a child with ADHD: a case of dacrystic seizures (Journal of Ideas in Health, 2025)
Background: Dacrystic seizures are uncommon epileptic events that manifest as brief episodes of uncontrollable crying. Because these episodes mimic emotional outbursts, they are often confused with behavioral or psychiatric problems, particularly in individuals with attention-deficit/hyperactivity disorder (ADHD).  Case presentation: We report the case of a 9-year-old boy with a medical history of ADHD who presented with recurrent, sudden crying spells without apparent triggers for nearly three years. The patient had no prior history of head trauma, central nervous system infection, or developmental regression. Neurological examination and brain magnetic resonance imaging (MRI) revealed no abnormalities, and routine laboratory tests were unremarkable. Following the exclusion of other possible etiologies, electroencephalography (EEG) conducted by a senior neurophysiologist in the pediatric neurology department confirmed the diagnosis of dacrystic epilepsy. The patient was started on a combination therapy of valproic acid (300 mg/day), lamotrigine (25 mg/day), and clonazepam (0.25 mg/day), which resulted in approximately 60% reduction in the frequency and intensity of the episodes within two months, without any significant adverse effects.Conclusion: Unexplained crying attacks in children, especially those with developmental disorders, should raise the possibility of dacrystic seizures. Careful neurological assessment and prompt use of antiepileptic therapy can markedly reduce symptoms and improve quality of life.
Keywords: Dacrystic Epilepsy, Ictal Crying, Pediatric Neurology, ADHD, Case Report, Iraq